Nomads in postrevolutionary Iran - Beck, Lois, 1944- (London ; New York)
xxv, 404 sayfa
Keywords: “Examining the rapid transition in Iran from a modernizing, westernizing, secularizing monarchy (1941-79) to a hard-line, conservative, clergy-run Islamic republic (1979-), this book focuses on the ways this process has impacted the Qashqa'i--a rural, nomadic, tribally organized, Turkish-speaking, ethnic minority of a million-plus people who are dispersed across the southern Zagros Mountains. Analysing the relationship between the tribal polity and each of the two regimes, the book goes on to explain the resilience of the people's tribal organizations, kinship networks, and politicized ethnolinguistic identities to demonstrate how these structures and ideologies offered the Qashqa'i a way to confront the pressures emanating from the two central governments. Existing scholarly works on politics in Iran seem unaware of, or uninterested in, Iranian society outside the capital of Tehran and beyond the reach of the details of national politics. Local-level studies on Iran--accounts of the ways people actually lived--are now rare, especially after the revolution. Based on long-term anthropological research, Local Political and Social Change in Iran provides a unique insight into how national-level issues relate to the local level and will be of interest to scholars and researchers of Anthropolgy and Iranian Studies.“ --